Application of nafamostat mesylate in 5 cases of extracorporeal carbon dioxide removal combined with continuous renal replacement therapy - Xiaobo, Ma; Qiuxin, Chen; Zhenhua, Yang; Xiaoting, Pan; Xiaonong, Chen (Frontiers in Pharmacology, 2025)
ObjectiveTo explore the application of nafamostat mesylate in the extracorporeal carbon dioxide removal combined with continuous renal replacement therapy.MethodWe analyzed the cases of 5 patients who underwent extracorporeal carbon dioxide removal combined with continuous renal replacement therapy due to severe hypercapnia with acute kidney injury at the Blood Purification Center of Ruijin Hospital Affiliated to Shanghai Jiao Tong University School of Medicine from July 2023 to October 2024. The treatments were performed using the OMNI blood purification system (B. Braun Avitum AG, Melsungen, Germany), equipped with a PMP polymethylpentene membrane lung (1.81 m2, Eurosets Medolla, Italy), with unhumidified pure oxygen connected to the ECCO2R membrane lung via an oxygen supply device at a rate of 6–7 L/min, and in series with the blood filter (OMNIFilter 16, polyethersulfone membrane, 1.6 m2). CRRT was performed using the CVVH mode, with sodium lactate replacement fluid at a flow rate of 2–3 L/h. A 14Fr dual-lumen dialysis catheter (ARROW) was placed under ultrasound-guided puncture in the femoral vein. The extracorporeal blood flow was maintained between 300 and 400 mL/min. Continuous infusion of NM (50-30 mg/h) was used to maintain anticoagulation. Demographic and physiological data were collected (including vital signs, ventilation parameters, blood gas, electrolytes, DIC, etc.), with blood sampling points before and after the filter as well as peripheral blood.ResultsAmong the 5 patients, there were 2 males and 3 females, with an average age of 83.2 ± 9.6 years old. A total of 22 treatments were administered, with an average treatment time of 8.8 ± 1.6 h. All patients had primary diseases of severe pneumonia and chronic obstructive pulmonary disease; among them, 4 had combined renal injury, and 3 patients were on mechanical ventilation. During the total of 22 treatments, there was 1 instance of dialyzing tube occlusion which led to the end of treatment 2 h early, while the other 21 treatments were completed smoothly, with no occlusion occurring in the filter, ECCO2R membrane lung, or dialyzing tube. No adverse events such as bleeding occurred in the patients, and there were no statistically significant differences in APTT and PT after treatment compared to before. During the treatment, statistically significant improvements in PaCO2 and blood pH were observed. Blood pressure, heart rate, and blood oxygen saturation remained stable.ConclusionExtracorporeal carbon dioxide removal combined with continuous renal replacement therapy can partially replace lung ventilation function and improve hypercapnia. NM can be used as an anticoagulant in this technology, with an ideal anticoagulation effect and no significant risk of bleeding.